High pressure plasma confinement and stability in gas dynamic trap - Ivanov, A.A.; Anikeev, A.V.; Bagryansky, P.A.; Karpushov, A.N.; Korepanov, S.A.; Kornilov, V.N.; Lizunov, A.A.; Maximov, V.V.; Murakhtin, S.V. (Вопросы атомной науки и техники, 2000)
The paper reviews recent results obtained in the studies of high beta plasma confinement in Gas-Dynamic Trap (GDT) device. Successful application of Ti -gettering and increase of NB injection power and duration enable to obtain a plasma as high as 30%. Enery balance and stability of this high beta plasma with a density of ~3 10¹³ cm⁻³ were thoroughly studied. Confinement of more dense plasma with steeper density gradients was also studied in the experiment with on-axis gas puff in the central cell.